2006
DOI: 10.1002/art.21790
|View full text |Cite
|
Sign up to set email alerts
|

Major reduction in spinal inflammation in patients with ankylosing spondylitis after treatment with infliximab: Results of a multicenter, randomized, double‐blind, placebo‐controlled magnetic resonance imaging study

Abstract: Objective. To determine whether the effects of anti-tumor necrosis factor ␣ (TNF␣) in reducing the signs and symptoms of ankylosing spondylitis (AS) coincide with a reduction in spinal inflammation as detected by magnetic resonance imaging (MRI).Methods. Pre-and postgadolinium T1 and STIR MR images of the spine were acquired at baseline and at week 24 in patients with AS who participated in a multicenter, randomized, double-blind, placebocontrolled study. Patients were randomly assigned at an 8:3 ratio to rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
105
0
17

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(126 citation statements)
references
References 23 publications
(38 reference statements)
4
105
0
17
Order By: Relevance
“…Several clinical studies have shown that etanercept reduces disease activity in patients with spondyloarthropathies, including reactive arthritis and AS [4][5][6][7][8]. Similar results have been reported with inXiximab, a chimeric monoclonal antibody against TNF [9][10][11][12][13][14][15]. The aim of the present work was to compare the eYcacy and safety of both etanercept and inXiximab in patients with ankylosing spondylitis in a two-year open label randomised study.…”
Section: Introductionsupporting
confidence: 57%
“…Several clinical studies have shown that etanercept reduces disease activity in patients with spondyloarthropathies, including reactive arthritis and AS [4][5][6][7][8]. Similar results have been reported with inXiximab, a chimeric monoclonal antibody against TNF [9][10][11][12][13][14][15]. The aim of the present work was to compare the eYcacy and safety of both etanercept and inXiximab in patients with ankylosing spondylitis in a two-year open label randomised study.…”
Section: Introductionsupporting
confidence: 57%
“…Treatment of patients with active AS using the currently approved TNF-blocking agents, infliximab (1), etanercept (2), and adalimumab (3), has been shown to be strongly effective for the improvement of signs, symptoms, and function and for the reduction of C-reactive protein levels and active inflammation in the sacroiliac joints and spine, as shown by magnetic resonance imaging (MRI) (4). TNF blockers have also been shown to be effective for control of extraspinal rheumatic manifestations and, with some differences between the TNF blockers, for amelioration of further AS-associated manifestations such as uveitis, colitis, and psoriasis (5).…”
Section: Introductionmentioning
confidence: 99%
“…The former are thought to evolve into Romanus lesions and the latter are thought to reflect spondylodiscitis. It has been shown that the severity of the MRI changes correlates with the histopathologic grading of inflammation (7), and reductions in active inflammatory lesions are readily visible on MRI within a few weeks following initiation of anti-TNF treatment (8)(9)(10).…”
mentioning
confidence: 99%